2008
DOI: 10.1016/j.jvs.2008.02.068
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal of velocity criteria for carotid bulb/internal carotid artery stenosis utilizing high-resolution B-mode ultrasound validated with computed tomography angiography

Abstract: Compared with established velocity thresholds commonly applied in practice, a substantially higher PSV (155 vs 125 cm/s) was more accurate for detecting > or =50% bulb/ICA stenosis. In combination, a PSV of > or =155 cm/s and an ICA/CCA ratio of > or =2 have excellent predictive value for this stenosis category. For > or =80% bulb ICA stenosis (NASCET 60% stenosis), an EDV of 140 cm/s, a PSV of > or =370 cm/s, and an ICA/CCA ratio of > or =6 are equally reliable and do not indicate any major change from the es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 34 publications
2
23
0
3
Order By: Relevance
“…We used planimetry to diagnose carotid restenosis of 50% to 69% because it provides an angiographic-like carotid stenosis measurement, with a good sonographic-angiographic agreement. [12][13][14][15][16][17][18] In addition, although there is a good agreement for severe stenosis between velocity parameters and planimetric data obtained by angiography or carotid ultrasound, 9,19,20 moderate stenoses are quantified less accurately by velocity parameters, 21 particularly in the setting of a multicenter study, which potentially increases variability of velocity measurements between centers. 9 In our study, the observed proportion of positive agreement between velocity and planimetric data were poor for the category of 50% to 69% restenosis (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used planimetry to diagnose carotid restenosis of 50% to 69% because it provides an angiographic-like carotid stenosis measurement, with a good sonographic-angiographic agreement. [12][13][14][15][16][17][18] In addition, although there is a good agreement for severe stenosis between velocity parameters and planimetric data obtained by angiography or carotid ultrasound, 9,19,20 moderate stenoses are quantified less accurately by velocity parameters, 21 particularly in the setting of a multicenter study, which potentially increases variability of velocity measurements between centers. 9 In our study, the observed proportion of positive agreement between velocity and planimetric data were poor for the category of 50% to 69% restenosis (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…The study protocol recommended that carotid ultrasound should be performed at 1,6,12,18,24, and 36 months after treatment and results should be recorded on a standardized study report form. The carotid ultrasound protocol included Doppler velocity measurements and B-mode imaging assisted by color-coded Duplex.…”
Section: Carotid Ultrasoundmentioning
confidence: 99%
“…Mild carotid stenosis was defined as a peak systolic velocity Ͻ125 cm/s at the site of maximal luminal narrowing on B-mode duplex ultrasonography 11 and a luminal diameter reduction of at least 30% on transverse B-mode duplex ultrasonography images. 12 Moderate stenosis was defined as a peak systolic velocity of 125 to 230 cm/s at the site of maximal luminal narrowing. 11 Exclusion criteria were atrial fibrillation or another potential cardiac source of embolism, contraindications for MRI, 13 and a renal clearance Ͻ30 mL/min/1.73 m 2 .…”
Section: Patientsmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18] A conventional linear array transducer (LAT) has a flat head with a high ultrasound frequency (> 7 MHz) and an ability to clearly and closely visualize detailed findings, such as hypoechoic plaques and plaque ulcerations in the carotid artery, from the broad surface of the neck. However, this approach sometimes has difficulty to achieve an appropriate ultrasonic view of the distal ICA, which is a denominator used in the NASCET measurement, especially in patients with high carotid artery bifurcation and a very short neck.…”
Section: Introductionmentioning
confidence: 99%